2008
DOI: 10.1303/aez.2008.617
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal abundance of hymenopteran parasitoids of the leafminer Chromatomyia horticola (Diptera: Agromyzidae) and the impact of insecticide applications on parasitoids in garden pea field

Abstract: The seasonal abundance of hymenopteran parasitoids reared from the agromyzid leafminer Chromatomyia horticola was monitored on garden pea in Shizuoka, central Japan, for 17 months between 2004 and 2005. The leafminer was abundant during the cool seasons (December to May) but parasitoid populations generally lagged behind the leafminer by approximately two months. Twenty-one parasitoid species were reared from C. horticola, and the most abundant parasitoid species were Diglyphus isaea, D. minoeus and Chrysochar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Abou-fakhr-Hammad (2000) reported that the population density of pea leafminer, L. huidobrensis was reduced by high daily average temperatures. Saito et al (2008) found that the garden pea leafminer, Chromatomyia horticola (Goueau) (Diptera: Agromyzidae), was abundant during the cool season in Japan. Homestead is located within a subtropical area, and the leafminer L. trifolii was more abundant when the average monthly temperature was relatively low (< 20 °C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abou-fakhr-Hammad (2000) reported that the population density of pea leafminer, L. huidobrensis was reduced by high daily average temperatures. Saito et al (2008) found that the garden pea leafminer, Chromatomyia horticola (Goueau) (Diptera: Agromyzidae), was abundant during the cool season in Japan. Homestead is located within a subtropical area, and the leafminer L. trifolii was more abundant when the average monthly temperature was relatively low (< 20 °C).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the reasons for the rapid increase in leafminer population densities include intensive insecticide applications leading to the development of resistance (Saito 2004) and reduction in natural enemy densities (Minckenberg & van Lenteren 1986). Other abiotic factors that may affect leaf miner population densities include temperature, light intensity and moisture (Shepard et al 1998;Saito et al 2008, Leibee 1986 Bordat et al (1995b) reported that 20 °C was optimal for both the adult male and female, and the optimum temperature for female reproduction was 25 °C. Light conditions could also affect leafminer density levels, and the pupariation of emergent L. trifolii larva can be delayed for a short time by continuous lighting condition (Leibee 1986).…”
mentioning
confidence: 99%
“…In Japan, L. chinensis and C. horticola are indigenous species while L. trifolii is an invasive species that was first reported in Japan in 1990 (Saito, 1993; Sasakawa, 1993). The pest status of these leafminers is compounded by their lack of susceptibility to insecticides (Parrella & Keil, 1984; Saito et al ., 1992, 1996, 2008 a ; Saito, 2004; Tokumaru & Okadome, 2004). A koinobiont parasitoid of leafminers, Halticoptera circulus (Walker) (Hymenoptera: Pteromalidae), is also resistant to the broad-spectrum insecticides, malathion (organophosphate) and tralomethrin (pyrethroid), and is, therefore, considered to have great potential as a biological control agent of leafminers within integrated pest management systems that include the use of insecticides (Saito et al ., 2008 a ; Matsuda & Saito, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The pest status of these leafminers is compounded by their lack of susceptibility to insecticides (Parrella & Keil, 1984; Saito et al ., 1992, 1996, 2008 a ; Saito, 2004; Tokumaru & Okadome, 2004). A koinobiont parasitoid of leafminers, Halticoptera circulus (Walker) (Hymenoptera: Pteromalidae), is also resistant to the broad-spectrum insecticides, malathion (organophosphate) and tralomethrin (pyrethroid), and is, therefore, considered to have great potential as a biological control agent of leafminers within integrated pest management systems that include the use of insecticides (Saito et al ., 2008 a ; Matsuda & Saito, 2014). However, H. circulus is rarely reported from L. trifolii in Japan (Saito et al ., 1996, 2008 b ; Arakaki & Kinjo, 1998; Amano et al ., 2008) while it is relatively abundant in L. chinensis and C. horticola populations (Takada & Kamijo, 1979; Tokumaru, 2006; Saito et al ., 2008 a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation